GC–MS analysis of bioactive compounds in methanolic leaf extract of Maerua oblongifolia (Forssk.) A. Rich. (2023) - Mukkamula, Nagaraju; Nagabhushanam, B.; Imran Mir, Mohammad; Sreekanth, D.; Kiran Kumar, B.
Abstract: Medicinal plants are rich sources of several diverse bioactive constituents with a wide range of biological effects. The screening of bioactive compounds plays a vital role in the protection of human health. Maerua oblongifolia (Forssk.) A. Rich., belonging to the family Capparaceae, is an important medicinal plant used in many ayurvedic formulations. The main aim of the current investigation was to study the phytochemical compounds in the leaves of M. oblongifolia using gas chromatography and mass spectrometry (GC–MS). The GC–MS study revealed the presence of 21 phytochemical compounds with high and low molecular weight chemical entities. The main bioactive compounds are hexadecenoic acid, methyl ester (RT-19.171; 2.03%), n -Hexadecanoic acid (RT-19.515; 2.07%), 13-Octadecanoic acid (RT-20.869; 2.49%) and Oleic acid (RT-21.209; 2.34%). The compounds have been identified by interpretation of the mass spectra. The presence of various bioactive compounds with diverse chemical structures confirms the application of leaves of M. oblongifolia for several diseases with fewer side effects. Hence, the plant is suggested as pharmaceutically important. Further, isolation of individual bioactive compounds may be necessary to find a novel drug.